2018
DOI: 10.21608/bvmj.2018.44199
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Effect of N-Acetylcysteine onApoptosis Associated with ImidaclopridInduced Testicular Damage inMale Albino Rats

Abstract: N-acetylcysteine (NAC), as a nutritional supplement, is a greatly applied antioxidant in vivo and in vitro. NAC is a precursor of L-cysteine that results in glutathione elevation biosynthesis. The therapeutic potential of N-acetylcysteine (NAC) has been investigated as a bioprotective agent against oxidative stress and ischemic injury. Also, it is used as a treatment for certain mental and physical illnesses. The aim of this study was to evaluate the protective and attenuating apoptosis effect of NAC on imidac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…pesticides) [90]. In line with our obtained results A Hussein, et al [91] and Abd-Elhakim, et al [92] observed an increase in the levels of MDA in imidacloprid intoxicated rats. Also, mice intoxicated with 30 mg/kg b.w./day of thiamethoxam for 28 days showed increase in the oxidative stress parameters such as MDA level in association with decrease in total antioxidants level [15].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…pesticides) [90]. In line with our obtained results A Hussein, et al [91] and Abd-Elhakim, et al [92] observed an increase in the levels of MDA in imidacloprid intoxicated rats. Also, mice intoxicated with 30 mg/kg b.w./day of thiamethoxam for 28 days showed increase in the oxidative stress parameters such as MDA level in association with decrease in total antioxidants level [15].…”
Section: Discussionsupporting
confidence: 90%
“…Otherwise, Tope and Panemangalore [18] discovered no differences in urine 8-OH-2DG levels between pesticide sprayers but detected higher levels in their plasma 8-OH-2DG samples when compared to the control. Also, A Hussein, et al [91] showed a significant increase in DNA damage detected by comet assay in imidacloprid intoxicated rats. Another study of MX-exposed zebrafish showed induction of oxidative stress and DNA damage which can be detected by the comet assay.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A MTT assay was performed to assess the cytotoxicity of GEEA extract against the lung cancer cell line A549. The cytotoxicity of various concentrations (20,40,60, 80 and 100 µg mL −1 ) of extract was assessed at different time points (12,18,24 and 48 h). The IC 50 value for the GEEA extract was calculated using EPA Probit analysis programme v1.5.…”
Section: Antiproliferative Activity Of Successive Extractsmentioning
confidence: 99%
“…The recent statistical reports reveal that lung cancer (85% of which is Non-small Cell Lung cancer (NSCLC)) is the second leading cause of death in the United States, Egypt and all other parts of the world. 12,26 In general, NSCLC is incurable because it develops acquired resistance after an initial response of chemotherapy and also develops intrinsic resistance to chemotherapy. 26 Currently, the discovering of potent bioactive agents is very much necessary to inhibit cell growth, target multiple signalling pathways and also to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%